Pengaruh Beban Kerja terhadap Kinerja Karyawan melalui Burnout Syndrome Pada PT. Perkebunan Nusantara X Pabrik Gula Tjoekir - Ayuk Rahmadyah (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This study aims to determine and analyze the effect of mediation variable burnout syndrome between workload on employee performance in PT. Perkebunan Nusantara X Pabrik Gula Tjoekir. This research is a type of research with a quantitative approach, with a population of permanent employees in PT. Perkebunan Nusantara X Pabrik Gula Tjoekir and the technique sampling with a sample saturated with a sample of 89 employees. The statistical analysis used in this study is Partial Least Square (PLS) analysis techniques and with software SmartPLS3. The statistical analysis tool in this study using the Partial Least Square (PLS) whit the software application SmartPLS3. The study results explained that workload has a positive and significant effect on employee performance, the workload has a positive and significant effect on burnout syndrome, burnout syndrome has a negative and significant effect on employee performance, and workload has no significant effect on employee performance through burnout syndrome. This study implies that if the company wants to improve employee performance, it must maintain environmental conditions, provide a portion of the work according to competence, control employee performance, and periodic job evaluation.